(untitled) (Research, Society and Development, 2025)
Introduction: Hyaluronic acid lip filling has become a frequent practice in facial aesthetics, and understanding its safety profile is essential to guide indication, informed consent, and complication management. Objective: To critically synthesize recent evidence on the efficacy and safety of lip augmentation with hyaluronic acid, focusing on the frequency, type, and severity of complications, as well as prevention and management strategies. Methods: Integrative review. Results and discussion: Hyaluronic acid showed consistent efficacy in lip augmentation, with high satisfaction and results lasting up to twelve months. The most common adverse events were pain, edema, and ecchymosis, usually mild and self-limiting. The risk of vascular occlusion is low but clinically relevant, being higher with needles than with cannulas. Dermatologic ultrasound proved useful for identifying and managing nonvascular complications, such as nodules and product migration, enhancing procedural safety. Conclusion: Lip augmentation with hyaluronic acid is effective and safe when performed with proper technique, careful instrument selection, and long-term clinical follow-up. Prevention, early diagnosis, and standardized protocols reduce the impact of complications and improve outcome predictability.